The primacy of the postils : Catholics, Protestants, and the dissemination of ideas in early modern Germany - Frymire, John M. (Leiden ; Boston : Brill, 2010)
Scholarship on the German Reformation has long equated preaching with Protestantism, just as many scholars have employed sermons but usually in supplemental and unsystematic ways. Based on an analysis of over 400 standard sermon collections (postils) produced by Catholics, Lutherans, and Calvinists (1520-1620), this study offers the first comprehensive, systematic presentation of these works from a cross-confessional perspective. It lays to rest the notion that preaching was somehow distinctively Protestant while tracing the creation, production, use, and censorship of postils.
Catholic preaching and the German Reformation? : postils and their production, 1520-1535 -- Re-invention, innovation, and reaction : Lutheran and Catholic postils, 1535-1555 -- Matches made in heaven : Lutheran postillators in the service of their princes, 1555-1620 -- Excursus : Calvinist postils? : the pragmatism of German Reformed postillators -- Catholic Postillenfresser : postils, Catholic reform, and the Counter-Reformation -- Correcting Catholicism : censorship, confessional consolidation, and the decline of homegrown postillators.
Includes bibliographical references (pages 559-631) and index.
Print version record.
Master record variable field(s) change: 610, 650, 651
Keywords: Catholic Church -- Sermons -- History and criticism; Catholic Church; Sermons -- Germany -- History and criticism; Germany -- Church history -- 16th century; Reformation -- Germany; RELIGION -- Christian Ministry -- Preaching; Reformation; Sermons; Germany; Postille; Deutschland; Geschichte 1520-1620; 1500-1599; Electronic books; Church history; Criticism, interpretation, etc